2020
DOI: 10.3390/metabo11010021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Organic Compounds in Mango Ginger (Curcuma amada Roxb.) from Myanmar

Abstract: Curcuma amada Roxb. (Zingiberaceae), commonly known as mango ginger because its rhizome and foliar parts have a similar aroma to mango. The rhizome has been widely used in food industries and alternative medicines to treat a variety of internal diseases such as cough, bronchitis, indigestion, colic, loss of appetite, hiccups, and constipation. The composition of the volatile constituents in a fresh rhizome of C. amada is not reported in detail. The present study aimed to screen and characterize the composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The conditions for the homogenization of samples were established following the previously reported methods, with some modifications [ 76 , 77 ]. An MB2000 Multi-bead Shocker (Yasui Kikai Co., Ltd., Osaka, Japan) was used to cryohomogenize the rhizome and leaf samples into fine powder by running into 2 circles at 2800 rpm for 16 s per round.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions for the homogenization of samples were established following the previously reported methods, with some modifications [ 76 , 77 ]. An MB2000 Multi-bead Shocker (Yasui Kikai Co., Ltd., Osaka, Japan) was used to cryohomogenize the rhizome and leaf samples into fine powder by running into 2 circles at 2800 rpm for 16 s per round.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not capable of quantifying the exact amount of each compound, and is mainly used to explore the overall composition of the target group of compounds [ 75 ]. HS-SPME and GC-TOF-MS have been successfully applied as the most modern methods in the metabolomic studies of Zingiberaceae species such as Curcuma amada and Zingiber barbatum [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2) ocimene, (3) β-farnasene, (4) cis-hydro-ocimene, (5) trans-hydro-ocimene, (6) α-longipinene, (7) α-guaiene, (8) linalool, (9) β-curcumene, (10) turmerone (11) curcumin, (12) bis-demethoxycurcumin, (13) demethoxycurcumin, (14) amadaldehyde, (15) betaasarone, (16) caffeic acid, (17) gentistic acid, (18) ferulic acid, (19) gallic acid, (20) cinnamic acid (Table 1) (3).…”
Section: Phytochemistrymentioning
confidence: 99%
“…And also submitted 10 potent antioxidant and highly available compounds such as alphazingiberene, alpha-tumerone, alpha-santelene, cuprene, (E)-gamma-atlantone, teresantol, beta-bisabolene, betasesquiphellandrene, gamma-curcumene trans-alphabergamotene. And they have found out that the Curcuma amada having more accession about (15.707± 5.78 a ) for the ZO89 compound as compared to Curcuma longa accession for ZO138 about (0.300± 0.08 a ) (19) Mamata Yadav et al, reported the in-vitro antioxidant activity of MG by using extract of rhizome in methanol against the DPPH assay by utilizing standard protocols. And by phytochemical analysis they also found out the presence of various constituents such as flavonoids, phenols, saponins, tannins and alkaloids, and the quantity of flavonoids in methanolic rhizome extract of the curcuma amada was detected to be 2.920mg/1000mg while as the curcuma longa was obtained to be 2.752mg/100mg, and this was concentration dependent with the IC50 value of ascorbic acid and extracts around 14.11 and 63.67µg/ml respectively (20) Devi P.A.V et al, have reported the antioxidant activity of the MG by carrying out the in-vitro cytotoxicity and free radical scavenging antioxidant activity of ethanolic extract of Curcuma amada.…”
Section: Collection Of Datamentioning
confidence: 99%
“…In addition to being used in the making of pickles, C. amada is also used as a source of raw mango flavour in meals and as a medicinal herb. The rhizome is important in Ayurveda, India's most important system of medicine, because it is an appetiser, alexteric, antipyretic, aphrodisiac, laxative and many more [3][4][5].…”
Section: Introductionmentioning
confidence: 99%